The Role of Ferritin as an Inflammation and Prognostic Marker in Systemic Infectious Diseases: A Litterature Review - Nurafni Maharani Nawawi; Irna Diyana Kartika Kamaluddin; Abbas Zavey Nurdin; Muhammad Jabal Nur; Akhmad Kadir (Journal La Medihealtico, 2026)
Systemic infectious diseases, including sepsis, COVID-19, and tuberculosis, remain major causes of morbidity and mortality worldwide and require reliable biomarkers for early risk stratification and prognosis. This literature review aims to evaluate the role of serum ferritin as an inflammatory and prognostic marker in systemic infectious diseases. This study used a systematic literature review design guided by the PICOS framework. Articles were identified through electronic databases, including PubMed, Google Scholar, ScienceDirect, ResearchGate, and other relevant sources, focusing on studies published between 2020 and 2026. The review included peer-reviewed full-text studies that measured serum ferritin levels and reported relevant clinical outcomes, such as disease severity, mortality, length of hospitalization, intensive care requirement, or inflammatory parameters. A total of 15 eligible studies were included in the synthesis. The findings showed that elevated serum ferritin is closely associated with systemic inflammation through cytokine-mediated pathways, macrophage activation, and neutrophil extracellular trap formation. In sepsis, high ferritin levels were consistently associated with increased mortality, longer intensive care stay, and multiorgan dysfunction. In COVID-19, ferritin was higher in severe cases and was related to ICU admission and mortality. In tuberculosis, ferritin was more relevant for monitoring treatment response and persistent infection. Overall, serum ferritin has important clinical value as an accessible and affordable biomarker for assessing inflammation, disease severity, and prognosis in systemic infectious diseases, although standardized cut-off values remain necessary for broader clinical application.